Robotic assistant spinal angiography: a case report and technical considerations. Issue 3 (10th March 2021) - Tateshima, Satoshi; Saber, Hamidreza; Colby, Geoffrey P; Enzmann, Dieter; Duckwiler, Gary
Abstract : Robotic-assisted technology has shown to be promising in coronary and peripheral vascular interventions. Early case reports have also demonstrated its efficacy in neuro-interventions. However, there is no prior report demonstrating use of the robotic-assisted platform for spinal angiography. We report the feasibility of the robotic-assisted thoracic and lumbar spinal angiography.